The Effects of Topic Familiarity on Kurdish EFL Students’ Lexical Inference Skill - Zheen Hamad Amin Abdullah; Nada Jabbar Abbas (Zanco Journal of Humanity Sciences)
The research examines the effect of topic familiarity on lexical inferencing. The independent variable includes a topic familiarity questionnaire and a test. At the beginning of the semester, the students are given a topic familiarity questionnaire to demonstrate the extent to which they are familiar with the topics from the book. Then, a pre-test is implemented, and students are asked to read the paragraphs and answer the questions. During the semester, the class’s cognitive strategies are implemented to teach the book’s texts. At the end of the semester, after completing seversl texts, the students sit for a post-test to display how much cognitive strategies assist them in improving their skills of word inferencing. They guessed the meanings of target words and completed an inference verification tasks to confirm or correct guesses and encourage deeper processing of target words. Analyses reveal a robust effects of topic familiarity on their lexical inferencing skills. The implications of the findings for lexical inferencing and processing through strategic reading tasks will be discussed more below.